Comparison of CCL28, interleukin‐8, interleukin‐1β and tumor necrosis factor‐alpha in subjects with gingivitis, chronic periodontitis and generalized aggressive periodontitis. (19th July 2012) - Ertugrul, A. S.; Sahin, H.; Dikilitas, A.; Alpaslan, N.; Bozoglan, A.
<x xml:space="preserve">Abstract</x> Background and Objective: Cytokines produced by various cells are strong local mediators of inflammation. Mucosa‐associated epithelial chemokine (CCL28), interleukin‐8 (IL‐8), interleukin‐1beta (IL‐1β) and tumor necrosis factor‐alpha (TNF‐α) are major cytokines that play important roles in the periodontal inflammatory process. In this study we aimed to compare the levels of CCL28, IL‐8, IL‐1β and TNF‐α in the gingival crevicular fluid of both periodontally healthy subjects and in subjects diagnosed with gingivitis, chronic periodontitis and generalized aggressive periodontitis. Material and Methods: A total of 84 subjects participated in the study: 21 subjects had gingivitis, 21 subjects had chronic periodontitis, 21 subjects had generalized aggressive periodontitis and 21 were periodontally healthy. The levels of CCL28, IL‐8, IL‐1β and TNF‐α were analyzed using enzyme‐linked immune sorbent assay (ELISA). Results: The total levels of CCL28 and IL‐8 in the gingival crevicular fluid of the generalized aggressive periodontitis group (324.74 ± 42.62 pg/30 s, 487.62 ± 49.21 pg/30 s) were significantly higher than those of the chronic periodontitis group (268.81 ± 28.64 pg/30 s, 423.65 ± 35.24 pg/30 s), the gingivitis group (146.35 ± 17.46 pg/30 s, 310.24 ± 48.20 pg/30 s) and the periodontally healthy group (92.46 ± 22.04 pg/30 s, 148.41 ± 24.64 pg/30 s). Similarly, the total levels of IL‐1β and TNF‐α in the generalized aggressive periodontitis group (110.23 ± 9.20 pg/30 s, 1284.46 ± 86.32 pg/30 s) were significantly higher than those in the chronic periodontitis group (423.65 ± 35.24 pg/30 s, 82.64 ± 9.12 pg/30 s), the gingivitis group (52.10 ± 7.15 pg/30 s, 824.24 ± 44.68 pg/30 s) and the periodontally healthy group (36.44 ± 8.86 pg/30 s, 628.26 ± 34.61 pg/30 s). Conclusion: CCL28, IL‐8, IL‐1β and TNF‐α may play key roles in the host response to inflammation in periodontal diseases. As the severity of periodontal diseases increases, destruction of periodontal tissues also increases. Inflammation is one among many factors that trigger periodontal tissue destruction. Identification of the mediators that influence the development and progression of inflammation in periodontal diseases may be very important in understanding the prognoses of periodontal diseases.